BALIMAU KASSAI DI DESA BATU BELAH KABUPATEN KAMPAR - Zulfa, Zulfa; Suri, Sofyan (Universitas Lancang Kuning, 2008)
This research aims of find out the meaning of a ritual called Balimau Kasai in Batu Belah village in Kampar regency. It is a qualitative research applying historical method. To get both primary and secondary data, some techniques are used, like; observation, interview, documentation and library study. The result of the research shows that the meaning of the ritual of Balimau Kasai is basically to purify oneself to welcome Ramadhan, the holy month of Islam, which is waited by most moslems, particularly by the community in Kampar. Unluckily, the impact of modernization affects the meaning if this ritualin which it changes the meaning of the purity of the Ramadhan by conducting the ritual differently from it should be.